The Effect of Confinement on Differential Leukocyte Count of Laying Pullets - AL-KHAZRAJI, A. K.; AL-JANABI, A. S.; LAWAND, S.; SHIRLEY, H.V. (The Libyan Journal of Agriculture, 2023)
Laying pullets were maintained under four housing conditions: in a floor pen, in 6" x 8" cages, and in 10" x 16" cages at the rate of one and two pullets per cage. Studies of leukocyte counts revealed small but non-significanl changes in the percent of certain cell types in association with the degree of confinement.